Chinese Mortgage Law: An American Perspective - Whitman, Dale A. (Columbia Journal of Asian Law, 2001)
The task of creating a system of law for real estate security interests is a daunting one – and all the more so if it must be done very quickly. The law of mortgages that prevails in the United States, the United Kingdom, and the other nations whose legal systems were derived from England has had the luxury of some 600 years of development. By contrast, the People’s Republic of China had little privately-owned real property, and hence little need for a law of real estate security, until 1988. From that time to the present, the Chinese government has been aggressively building a system of real estate finance that can support private ownership of property. In general, this effort has been remarkably successful and stands as a great compliment to its drafters. Loans on the security of houses, apartments, and commercial land and buildings are made every day, and without doubt have contributed vastly to the economic development of China during the past decade. At the same time, however, Chinese mortgage law has a number of serious problems – features which are either uncertain in operation, or which are unnecessary stumbling blocks to the smooth and efficient functioning of the market in real estate financing.